Freud and the changing world : contemporary psychoanalysis and its troubles - Bolognini, Stefano; Nicoli, Luca (Karnac Books, 2025)
A highly original, convivial dialogue between two leading psychoanalysts invites the reader to pause and reflect on current transformations and emotional affects in a changing world. Two analysts of different generations dialogue openly on the psychoanalytic experience, the relationship between patient and analyst, and the setting that continually comes to life in the session. Key themes discussed include social changes, the need to emotionally tune in to the distrust of today's patients, online therapies, public mental health services, and new forms of sexuality and relationships. The heart of the book deals with major changes in psychoanalysis, whereby 'how' to talk to patients and how to approach them is just as important as 'what' is said in the consulting room. The limited use of technical terms promotes the book's usability in every chapter and makes it accessible to every type of reader. Where technical terms are inescapable, a useful glossary is provided to explain these key concepts, providing clarity and understanding of the psychoanalytic field. The perfect book to illuminate the continuing contribution of psychoanalysis to the world.
Originally published in 2022 in Italian as Freud e il mondo che cambia. Psicoanalisi del presente e dei suoi guai by Enrico Damiani Editore e Associati.
Keywords: Psychoanalysis.; Psychanalyse.; psychoanalysis.; PSYCHOLOGY / Movements / Psychoanalysis